Entrepreneurship in a global context - Birley, Sue; MacMillan, Ian C., 1940- (Routledge studies in international business and the world economy ;, 1997)
This collection presents selected papers from the Fourth Annual Global Conference on Entrepreneurial Research, held in 1994 at INSEAD, France.